They can’t safeguard you when they are under stress: An exploratory study on issues and problems of job stress in police - Nisar, Sehran Khan (International journal of police science & management, 2018)
The purpose of this research is to explore work-related stress in the police of Azad Jammu and Kashmir (AJ&K), Pakistan. The research aims to identify factors that contribute most towards job stress in AJ&K police and study the nature of and reasons underlying these factors. Political and media pressure has not been widely studied within the context of job stress in the police, and researchers have attempted to bridge this gap and make a theoretical contribution by highlighting the importance of political and media pressure as a job stressor for the police profession. This is exploratory research in which a survey was conducted in three large cities of AJ&K, Pakistan. Primary data was collected through a questionnaire comprising closed and open-ended interview questions. Descriptive statistics, correlation and regression analysis were conducted using SPSS. Content analysis of the interview statements was also undertaken to enhance the validity of the study. The research findings showed that although lack of resources is the biggest issue, other factors like political and media pressure, and long working hours are also significantly and positively associated with job stress in the police in AJ&K. The article draws attention towards political and media pressure as a job stressor for police. The research has an important role in compelling top management in AJ&K police to ponder the issue of job stress within their department. The findings are also important for police in other countries who are facing similar issues.